Considerations towards illicit drug use and trafficking in Romania - Rus, Mihaela; Sandu, Mihaela Luminita; Matei, Raluca Silvia; Rus, Ciprian; Tasente, Tanase (Technium Social Sciences Journal, 2021)
Consumption and drug trafficking are worldwide recognized as a dynamic phenomenon influenced by various factors such as social and economic. Also in Romania, drug use and trafficking present new forms of manifestation, being known as a complex phenomenon, characterized by permanent mutations. Twenty years ago, Romania was known as a state where drugs were only transited, but in the last ten years, our country has been transformed into a market for drug use, especially heroin.